2017
DOI: 10.1186/s13148-017-0318-6
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation levels are altered by modifiable clinical manipulations in assisted reproductive technologies

Abstract: BackgroundWe analyzed placental DNA methylation levels at repeated sequences (LINE1 elements) and all CCGG sites (the LUMA assay) to study the effect of modifiable clinical or laboratory procedures involved in in vitro fertilization. We included four potential modifiable factors: oxygen tension during embryo culture, fresh embryo transfer vs frozen embryo transfer, intracytoplasmic sperm injection (ICSI) vs conventional insemination or day 3 embryo transfer vs day 5 embryo transfer.ResultsGlobal methylation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 61 publications
5
64
0
1
Order By: Relevance
“…A particular strength of this study is that the embryos in both IVF groups were transferred into physiologic hormonal environments, thus minimizing the confounding effects of superovulation on the endometrium. Several other studies have reported similar patterns in other genes related to growth, with frozen embryos yielding epigenetic patterns and gene expression more similar to natural conception (Estill et al, ; Ghosh, Coutifaris, Sapienza, & Mainigi, ). This suggests a potential mechanism of vitrification resulting in reversal of the epigenetic effects of superovulation on the oocyte, with consequentially larger babies.…”
Section: Proposed Mechanismsmentioning
confidence: 61%
“…A particular strength of this study is that the embryos in both IVF groups were transferred into physiologic hormonal environments, thus minimizing the confounding effects of superovulation on the endometrium. Several other studies have reported similar patterns in other genes related to growth, with frozen embryos yielding epigenetic patterns and gene expression more similar to natural conception (Estill et al, ; Ghosh, Coutifaris, Sapienza, & Mainigi, ). This suggests a potential mechanism of vitrification resulting in reversal of the epigenetic effects of superovulation on the oocyte, with consequentially larger babies.…”
Section: Proposed Mechanismsmentioning
confidence: 61%
“…Periconceptional developmental programming (ie, embryonic developmental decisions) can also be influenced by a broad spectrum of conditions other than maternal nutrition. These include maternal age, xenobiotic exposures, and conditions of exposure during in vitro fertilization and assisted reproductive technologies (ARTs) . These have all been associated with increased long‐term risk of cardiometabolic dysfunction in human as well as in animal models.…”
Section: A Compelling Animal Model Of Fetal Programmingmentioning
confidence: 99%
“…These include maternal age, 19 xenobiotic exposures, 1,2 and conditions of exposure during in vitro fertilization and assisted reproductive technologies (ARTs). 22,23 These have all been associated with increased long-term risk of cardiometabolic dysfunction in human as well as in animal models. To minimize the risk of heritable noncommunicable, nongenetic, or DOHaD diseases, there must be greater resources directed toward preconception care and preparation for pregnancy to protect the health of the next generation as well as those that follow.…”
Section: A Compelling Animal Model Of Fetal Programmingmentioning
confidence: 99%
“…Taking one step further, Scott Morin then tackles the question of oxygen tension in the context of spatial and temporal changes that the conceptus might be expected to face within confines of the reproductive tract [10]. Interestingly, a recent publication identifies oxygen tension as having an important influence on global DNA methylation patterns when embryos cultured at 5 or 20% were compared [11].…”
Section: Commentarymentioning
confidence: 99%